Implementasi penataan kelas formasi â€œuâ€ dalam rangka meningkatkan hasil belajar PKN pada materi sikap patuh pada tata tertib Siswa kelas III Min Baet - Munawar, Munawar (Jurnal Pendidikan dan Pengabdian Vokasi (JP2V), 2020)
The purpose of this class action research is to find out whether or not there is a significant influence on the arrangement of "U" seating formation on student learning outcomes in Civics Class III MIN Baet subjects in the Academic Year 2017/2018. The method used in this classroom action research is the method of structuring the formation of students' seating. Seating formations are many types, one of which is the U seat formation, with this formation it is expected that students will not get bored in learn-ing, more active due to variations in learning. The methodology of this research is Classroom Action Research consisting of two cycles and each cycle consists of two meetings. In each cycle consists of planning, implementation, observation and reflection. The research procedure consisted of pre-research, planning cycle one, implementing cycle one, observing cycle one, reflection cycle one, planning cycle two, implementing cycle action two, observing cycle two and reflection cycle two. Data collection tech-nique is to collect the value of the test carried out at the end of each learning in each cycle using the question instrument (written test). Observation data is done by observing the activeness of students in the learning process. Data were analyzed by means of percentage statistics. The results showed that an increase in completeness of student learning outcomes from 73.68% in Cycle I and increased to 89.47% in Cycle II. The implementation of structuring the "U" formation class can improve the learning out-comes of Civics in material adherence to the discipline of students in class III MIN Baet for the 2017/2018 Academic Year.